Rapid high yield production of different glycoforms of Ebola virus monoclonal antibody. - Alexandra Castilho; Natasha Bohorova; Josephine Grass; Ognian Bohorov; Larry Zeitlin; Kevin Whaley; Friedrich Altmann; Herta Steinkellner (PLoS ONE)
Background Fc-glycosylation of monoclonal antibodies (mAbs) has profound implications on the Fc-mediated effector functions. Alteration of this glycosylation may affect the efficiency of an antibody. However, difficulties in the production of mAbs with homogeneous N-glycosylation profiles in sufficient amounts hamper investigations of the potential biological impact of different glycan residues. Methodology/principal findings Here we set out to evaluate a transient plant viral based production system for the rapid generation of different glycoforms of a monoclonal antibody. Ebola virus mAb h-13F6 was generated using magnICON expression system in Nicotiana benthamiana, a plant species developed for commercial scale production of therapeutic proteins. h-13F6 was co-expressed with a series of modified mammalian enzymes involved in the processing of complex N-glycans. Using wild type (WT) plants and the glycosylation mutant ΔXTFT that synthesizes human like biantennary N-glycans with terminal N-acetylglucosamine on each branch (GnGn structures) as expression hosts we demonstrate the generation of h-13F6 complex N-glycans with (i) bisected structures, (ii) core α1,6 fucosylation and (iii) β1,4 galactosylated oligosaccharides. In addition we emphasize the significance of precise sub Golgi localization of enzymes for engineering of IgG Fc-glycosylation. Conclusion The method described here allows the efficient generation of a series of different human-like glycoforms at large homogeneity of virtually any antibody within one week after cDNA delivery to plants. This accelerates follow up functional studies and thus may contribute to study the biological role of N-glycan residues on Fcs and maximizing the clinical efficacy of therapeutic antibodies.